Biomechanical report for the IAAF World Championships London 2017 discus throw women's - Bennett, T.; Walker, J.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The women`s discus final took place on the evening of August 13th in favourable weather conditions. Sandra Perkovic from Croatia was a strong favourite going into the final having produced a personal best and world leading throw of 71.41 m before the championships. Perkovic displayed a dominant performance from the start with a leading throw of 69.30 m in the first round, before consolidating victory with an improved throw of 70.31 m in the second round. The closest challenger to Perkovic was Dani Stevens from Australia, who produced a national record throw of 69.64 m in the final round to win the silver medal. The bronze medal went to Mélina Robert-Michon from France with a season`s best throw of 66.21 m in the final round. (Attention! registration on the IAAF site is required for downloading)